Medical Skills in a Clinical Presentation-Based Curriculum - Approach to Acute Sore Throat - Gordon Woods (Association of American Medical Colleges, 2015)
Abstract The materials in this resource will guide clinical faculty as they organize and present a learning session for preclerkship medical students on the evaluation of a patient with an acute sore throat. During the session, students individually (or in pairs) interview a young adult standardized patient (SP) who presents with acute sore throat. After the encounter, students write a subjective, objective, assessment, and plan (SOAP) note, receive feedback from the SP, receive feedback from their peer observer (if available), and debrief in a group discussion with a faculty member. The submitted materials include a readiness assurance quiz, preparatory exam room guide and video, summary outline that students can use during the SP encounter, a check sheet to guide peer observer feedback, and a SP case blueprint. Additionally, there is a supplemental Spanish translation of the patient encounter. These materials would be of interest to clinical skills instructors who would like to hold a learning session for preclerkship students on bedside communication skills, evidence-based clinical decision-making, and basic documentation skills. These materials were originally developed for the Medical Skills Course at the Texas Tech University Paul L. Foster School of Medicine (PLFSOM) in El Paso, Texas. For this learning activity, history-taking and physical examination are structured around the framework of an evidence-based clinical decision-making rule, the modified Centor score. This rule helps students to organize their interview and exam, and helps to prevent them from falling back on intuition and educated guessing to guide their workup. Importantly, the decision rule demonstrates to students early in their training that evidence-based decision tools can improve their efficiency while increasing diagnostic accuracy. Additionally, this straightforward, low risk, SP encounter creates a good platform for students to practice their verbal and nonverbal communication skills. Finally, this encounter also provides a learning opportunity on the importance of patient safety, as instruction highlights that they must check for rare but potentially dangerous diagnoses that can present as sore throat.